PENGARUH SUBSTITUSI SARI BUAH NAGA MERAH TERHADAP DAYA TERIMA DAN TOTAL FLAVONOID SUSU NABATI BERBAHAN DASAR BIJI JALI - Omyning Pratiwi, (2020)
Non-communicable diseases are diseases that occur due to decreased function of chronic body organs caused by the aging process or chronic inflammation.World Health Organization (WHO) predicts that in 2030 the number of deaths due to non-communicable diseases will be 52 million people per year compared to 2018 which only 38 million people.The purpose of this study was to analyze the formula for the substitution of red dragon fruit extract on the sensory acceptance and total flavonoids of vegetable milk made from job's tears seeds. The method in this study was experimental with a completely randomized design (CRD) one factor with two repetitions.The formula was divided into 4 with each level of substitution percentage of red dragon fruit extract of F0 (0%), F1 (15%), F2 (20%), and F3 (25%). Organoleptic test analysis used the Kruskall Wallis test and continued with the Mann Whitney test.Analysis of total flavonoidused the ANOVA test and followed by Duncan test. The results of the organoleptic test analysis of the substitution of red dragon fruit extract had a significant effect (p <0.05) on the degree of color preference.Based on the total flavonoid analysis test the substitution of red dragon fruit extract has a significant effect (p <0.05) on vegetable milk based on job's tears seeds. The chosen formula wasF3 which has energy (41.4%), protein (0.68%), fat (0.49%), carbohydrate (8.57%), ash content (0.1%), water content (225.5%) total flavonoids (1540 mg) and viscosity of 11.25 cPoice at 250 ml serving sizes.